Outcome of children with systemic rheumatic diseases admitted to pediatric intensive care unit: An experience of a tertiary hospital - Al-Mayouf, Sulaiman M (Int J Pediatr Adolesc Med, 2019)
OBJECTIVE: To report the outcome of children with rheumatic diseases admitted to pediatric intensive care unit (PICU) in a tertiary hospital. METHODS: Database from PICU and pediatric rheumatology section used to retrieve all candidate patients admitted to PICU from June 2000 to December 2017. Medical records of all enrolled patients reviewed for diagnosis, organ involvement, reason of PICU admission, the length of stay, and outcome. RESULTS: Twenty-five patients (17 female, 8 male) with total of 41 admissions identified. The median PICU stay was 13.5 days (range, 3–24). The most frequent diagnoses were systemic lupus erythematosus (SLE) (48%), followed by systemic vasculitis (16%). Most admissions were from the medical ward (68.3%), while 24.4% from the emergency room. The main reason of PICU admission was a disease flare or related complications (48.8%), followed by infection (34.2%). Fifty one percent of the admissions were due to respiratory dysfunction, 46% required non-invasive respiratory support while 38% was in need for mechanical ventilation. During PICU stay, anti-microbial agents used 90.3%, immunosuppressive treatment adjustment 75.6%, anti-hypertensive 24.4% and vasopressors 12.2%. Twelve patients (48%) fully recovered and 40% partially recovered while three patients died during their PICU stay. The causes of death were macrophage activation syndrome complicated by sepsis in two patients and advanced pulmonary hypertension in one patient. CONCLUSION: Our data showed that children with rheumatic diseases, particularly SLE, are mostly admitted to PICU with serious disease exacerbation or severe infection. To improve the outcome, early diagnosis of critical condition and proper intervention are fundamental in reducing mortality.